TAKAFUL BUSINESS MODEL AND BUSINESS PERFORMANCE: A COMPARATIVE EVIDENCE FROM THE GLOBAL TAKAFUL INDUSTRY (International Journal of Islamic Business, 2024)
As a means for takaful operators to survive and sustain their business within the industry, they must appropriately choose takaful business models for their products. Different types of takaful business models will determine the different types of income for the business. Thus, this study aims to identify the most competitive takaful business model that relies on the takaful operators’ business performance. This study employed qualitative and quantitative methods on eight selected global takaful operators. The qualitativemethod is employed through content analysis to identify the application of the Shariah contract and the respective standards. Meanwhile, the quantitative method analyzes each takaful operator’s business performance (profit-after-tax and the return on assets). The finding indicates that three out of eight operators adopted the wakalah-mudarabah model, two operators with the wakalah model, two with the wakalah-waqf model, and one with the wakalah-qard model. The finding also highlights that Syarikat TakafulMalaysia Keluarga Bhd recorded the highest profit-after-tax average and the average of return on assets using a wakalah-qard model. This study betrays an exigent insight into the effect of takaful business model selection on business performance. As a practical implication to the takaful operators, they need to restrategize their business model to boost revenue through an appropriate model. This study also provides a breakthrough to the body of knowledge. This paper bids its originality by narrowing down the segment ofthe takaful industry and focusing only on the family takaful segment.